Tannic acid modified iron oxide nanoparticles and its application in protein adsorption: isotherm, kinetic, and thermodynamic study (Universitas Jenderal Soedirman, 2022)
Iron oxide nanoparticles, such as Fe3O4, are commonly used in various applications, such as drug delivery, magnetic fluid, water purification, and enzyme immobilization. These applications require protein to be adsorbed on the surface of iron oxide nanoparticles. However direct utilization of iron oxide nanoparticles has several drawbacks, thus modification of iron oxide nanoparticles is usually done. In this study, we reported surface modification of Fe3O4 using tannic acid to adsorb bovine serum albumin (BSA). The effect of modification and the BSA adsorption on the Fe3O4 was characterized using Fourier Transform Infrared Spectroscopy, X-ray Diffraction, Scanning Electron Microscopy, and Transmission Electron Microscopy. Furthermore the adsorption performance of modified and unmodified Fe3O4 was investigated at various initial pH, BSA concentration, and adsorption temperature. Several kinetic and isotherm adsorption models were used to describe the adsorption in this study. It was found that highest BSA adsorption was obtained at pH 4.8, near BSA’s isoelectric point. The adsorption kinetics followed the pseudo 2nd order model and reached equilibrium after 210 min adsorption. Based on Langmuir monolayer adsorption capacity, it was found that tannic acid modified Fe3O4 had 5 times higher adsorption capacity (222 mg/g), compared to unmodified Fe3O4 (46 mg/g). Furthermore, from the thermodynamic study, it was suggested that the BSA adsorption was endothermic, spontaneous, and random in nature.